HUVECs with KNDC1 knockout mediated by CRISPR/Cas9 have anti-aging ability - SUN Jing-yu, YAO He, HU Gang, WEI Jie, GUO Jun, ZHANG Xin, LIN Ya-jun (Jichu yixue yu linchuang, 2020)
Objective To knock out the KNDC1 of human umbilical vein endothelial cells (HUVECs) by CRISPR/Cas9 gene editing technology and observe its anti-aging ability. Methods Five sgRNAs targeting KNDC1 Exon1, Exon2 and Exon3 were designed by online software and were constructed into CRISPR/Cas9 vector. After sequence confirmation, the recombinant plasmids were transfected into HeLa cells and HUVECs. After 48 h, KNDC1 mRNA levels and protein expression levels were detected by real-time PCR and Western blot; cell senescence was measured by SA-β-gal staining; intracellular reactive oxygen species were detected by 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) fluorescent probe. Results The sequencing results showed that all the 5 sgRNAs were inserted into the CRISPR/Cas9 vector, the sequence was correct and these vectors were successfully constructed. After transfecting 5 recombinant vectors into HeLa cells, it was found that the knockout efficiency of vectors No. 4 and No. 5 was higher, and then the recombinant vectors of No. 4 and 5 were transfected into HUVECs. Compared with the control plasmid, the KNDC1 mRNA level and protein expression level in HUVECs transfected with recombinant plasmids 4 and 5 were significantly decreased (P＜0.05). The number of senescent HUVECs and the level of intracellular reactive oxygen species were significantly reduced. Conclusions The KNDC1 of HUVECs can be effectively knocked out by CRISPR/Cas9 technology, and HUVECs with KNDC1 knockout have anti-aging ability.